LITERACY ACTIVITIES OF SPECIAL NEED STUDENT: A CASE STUDY IN SOLVING READING COMPREHENSION FOR ADHD STUDENT - Aquariza, Novi Rahmania (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2018)
Language teachers have many ways to make the teaching and learning process become more interesting, especially in teaching the students with the special need. One of this types known as ADHD (Attention Deficits Hyperactive Disorder) will be discussed in this paper. The student with this type of special need has a special ways too in their teaching and learning process. In this case, reading comprehension. Reading is well known as one of the literacy activities. Make thestudents literate is very important no matter who the student is. Thus the special need student also has a right to be literate too through the literacy activities. This paper focuses on describing the teaching and learning process of reading using comic strip. The discussion is about the way itconducts in a class, the steps and also the materials used. The data were collected by documentation, observation, and interview; and, analyzed using qualitative description. The results show that comic strip is able to build an enthusiasm of the student. It is because comic strip is interesting for him. It automatically helps him to predict the content of the text given. Thus, through the use of comic strip, the problems related to the reading comprehension of special need students are solved gradually